Algebra to go : a mathematics handbook - Kaplan, Andrew (Wilmington, MA : Great Source Education Group, 2000)
Presents a handbook to assist Algebra students with math prefixes and suffixes, study tips, test-taking strategies, helpful tables, and graphing calculator directions.
Includes index.
Young Adult
Keywords: Algebra; Mathematics -- Handbooks, manuals, etc; Algebra; Mathematics -- Handbooks, manuals, etc